Genome editing: An alternative to retroviral vectors for Wiskott-Aldrich Syndrome (WAS) Gene Therapy?. (3rd March 2016) - Martin, F.; Gutierrez-Guerrero, A.; Sánchez, S.; Galvani, G.; Benabdellah, K.
Abstract: Introduction : Hematopoietic stem cells (HSCs) transduced with retroviral vectors (RVs) have shown good therapeutic efficacy in Wiskott-Aldrich Syndrome (WAS). However, RVs integrate randomly into the genome of HSCs which represents a potential safety concern. In this context, gene correction using genome editing (GE) technologies has been proposed as a possible alternative to integrative retroviral vectors. Areas covered : Lentiviral vectors (LVs) have obtained the best results in clinical trials for WAS gene therapy. In this review we will describe the different tools used for GE. The efficiency and safety of WAS gene correction will be put in context with the results obtained with LVs. Expert opinion In spite of their excellent results in recent WAS clinical trials, LVs integrate randomly into the genome and can therefore produce undesired side effects. WAS gene correction by GE could, in theory, avoid these potential problem. However, the low efficiency of gene correction in HSCs hampers the applications of this technology for WAS GT. We can therefore state that LVs are still the tool of choice for WAS gene therapy.